2013
DOI: 10.2174/15701786113109990035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Semisynthetic Anion Receptor: Synthesis and Ion Recognition of (1-H-pyrrol-2-yl)-4-oxo-perezone

Abstract: We describe the synthesis of the novel 2-(1,5-dimethyl-4-oxo-hexyl)-3-hydroxy-5-methyl-6-pyrrolyl-1,4-benzoquinone 2 from the natural product perezone 1. The anion–guest properties of the new compound were evaluated in the presence of fluoride, chloride, bromide and iodide tetrabutylammonium salts using 1H NMR titration techniques in deuterated dichloromethane or dimethylformamide. The title compound showed interesting colorimetric behavior in the presence of inorganic salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Compound 2 was synthesized by the addition of pyrrole to perezone 1 using SiO 2 as the acid promoter of the reaction, as reported previously for compound 3 ; 40 the latter compound was used as a control for ion sensing. Dipyrromethane derivative 4 was obtained as a blue-violet amorphous solid by using a green approach to the condensation of (1 H -pyrrol-2-yl)-4-oxo-perezone 3 , with acetone catalyzed by dilute HCl ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 2 was synthesized by the addition of pyrrole to perezone 1 using SiO 2 as the acid promoter of the reaction, as reported previously for compound 3 ; 40 the latter compound was used as a control for ion sensing. Dipyrromethane derivative 4 was obtained as a blue-violet amorphous solid by using a green approach to the condensation of (1 H -pyrrol-2-yl)-4-oxo-perezone 3 , with acetone catalyzed by dilute HCl ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Perezone derivatives 2 and 4 have been designed to recognize ion pairs and act as colorimetric sensors, as it was reported previously for compound 3 , where color changes can be observed for several ion pairs; 40 before using these compounds toward charged species, we compared the differences at their UV/vis absorption spectra, observing no other significant changes than a slight increase in absorbance and a bathochromic shift for the ICT transition band suffered by compound 4 , as shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group reported a novel pyrrolyl quinone system obtained from the natural product perezone or from 2,5-dimethyl-1,4-benzoquinone (Scheme 1), which showed an ability to carry out aldehyde oxidative amidation reactions, as well as being efficiently recognized by the fluoride ion when treated with tetrabutylammonium fluoride (TBAF) solution. [11][12][13] The synthesis of the pyrrolyl quinone 8 (R 1 = H; R 2 = Me), when obtained from dimethylbenzoquinone 7 (R 1 = H; R 2 = Me) and pyrrole, gave a 4% yield of the secondary product 9 through addition of pyrrole to the most-substituted position of the quinone (Scheme 1). In an attempt to evaluate the fluoride-recognition capacity of compound 9 toward TBAF, we carried out trials by following its titration course using 1 H NMR spectroscopy in CD 3 CN, as shown in Figure 2.…”
Section: Cluster Synlettmentioning
confidence: 99%
“…This compound displayed good specicity toward uoride binding. 19 These results led us to design receptor 2 in an attempt to probe the efficacy of the anion-p interactions. We focused on a two-point recognition motif and utilized both a hydrogen bonding dipyrrolyl group and an electron-decient redox-active quinone-based chromophore.…”
mentioning
confidence: 99%